Organic Waste Processing Training for Members of the Pusat Informasi dan Konseling Remaja (PIK-R) Bukit Gado-Gado Padang as an Effort for Sustainable Environmental Education - Anggriyani, Ria; Alberida, Heffi; Fajrina, Suci; Rahmatika, Helsa (Fakultas MIPA Universitas Negeri Padang, 2024)
The accumulation of waste that occurs in Indonesia is dominated by domestic organic waste. This also happened in Bukit Gado-Gado Padang which is exacerbated by the geographical conditions which are hilly areas, so that people have difficulty accessing temporary waste disposal sites which are far from the top of Bukit Gado-Gado. This problem is the impact of a lack of public awareness about the importance of maintaining environmental cleanliness and a lack of knowledge and skills in processing domestic waste. One effort to educate the public is through educating young men and women who are members of Pusat Informasi dan Konseling Remaja (PIK-R) Bukit Gado-Gado about processing domestic organic waste into environmentally friendly and economically valuable materials, namely solid organic fertilizer (compost) and liquid organic fertilizer. The methods used in this activity are lectures, demonstrations, questions and answers and guided practice. The results of the evaluation of this activity show that there is an increase in the knowledge, skills and motivation of participants in processing organic waste to preserve the environment.